2014
DOI: 10.1292/jvms.13-0635
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Selected Cytokine Gene Expression in Colonic Mucosa from Dogs with Idiopathic Lymphocytic-plasmacytic Colitis

Abstract: Lymphocytic-plasmacytic colitis (LPC) is a common form of inflammatory bowel disease (IBD) affecting the canine large intestine. Cytokines are thought to be involved in the pathogenesis of IBD. However, to date, few studies have investigated cytokine mRNA expression in dogs with LPC. In this study, we investigated mRNA transcription levels of T helper cell cytokines, such as IFN-γ, IL-4, IL-17 and IL-10 and pro-inflammatory cytokines, such as IL-1β, IL-6, TNF-α, IL-8, IL-12 and IL-23, in colonic mucosa from LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Several studies have investigated cytokine profiles in the duodenal and colonic mucosa of dogs with IBD at mRNA or protein levels, but consistent results have not yet been obtained . A previous study reported absolute and relative increases in IL‐1β in the duodenal mucosa of dogs with IBD .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Several studies have investigated cytokine profiles in the duodenal and colonic mucosa of dogs with IBD at mRNA or protein levels, but consistent results have not yet been obtained . A previous study reported absolute and relative increases in IL‐1β in the duodenal mucosa of dogs with IBD .…”
Section: Discussionmentioning
confidence: 98%
“…All dogs showed both small and large bowel diarrhea with or without vomiting. The median CCECAI score was 7 (range, [3][4][5][6][7][8][9][10][11][12][13][14]. The median WSAVA scores in the duodenum and in the colon were 10.5 (range, 6-17) and 4 (range, 2-9), respectively.…”
Section: Clinical and Histopathological Characteristics Of Dogs Witmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports describe various components of the cytokine signature (interleukin [IL]‐1β, IL‐2, IL‐4, IL‐5, IL‐6, IL‐8, IL‐10, IL‐12p40, IL‐17, IL‐18, IL‐23, IL‐25, IL‐33, IFN‐γ, TNF‐α, and TGF‐β1) in dogs with CIE,137, 138, 139, 140, 141, 142, 143 all of which do not support a Th1 nor Th2 polarization as described for inflammatory bowel diseases in humans 144, 145. There also is no evidence of a Th17 signature in dogs with CIE 146, 147.…”
Section: Biomarkers In Chronic Inflammatory Enteropathies Of Dogsmentioning
confidence: 99%
“…135 The lack of a correlation between serum sRAGE and S100A12 concentrations suggests that sRAGE is a nonspecific decoy receptor in dogs. 27 Similar to inflammatory bowel disease in humans, 136 [IL]-1β, IL-2, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12p40, IL-17, IL-18, IL-23, IL-25, IL-33, IFN-γ, TNF-α, and TGF-β1) in dogs with CIE, [137][138][139][140][141][142][143] all of which do not support a Th1 nor Th2 polarization as described for inflammatory bowel diseases in humans. 144,145 There also is no evidence of a Th17 signature in dogs with CIE. 146,147 One problem with using cytokines as biomarkers in dogs is that there are many cytokine assays available.…”
Section: Soluble Receptor For Advanced Glycation End Productsmentioning
confidence: 99%